Polybutylene succinate (PBS)/natural fiber green composites: melt blending processes and tensile properties - Shamsuri, Ahmad Adlie; Abdan, Khalina; Jamil, Siti Nurul Ain Md. (Walter de Gruyter GmbH, 2022)
An increase in the environmental consciousness at present has enhanced the awareness of researchers in utilizing biodegradable materials for the production of environmentally friendly products. Currently, biodegradable polymers, for example, polylactic acid, polybutylene succinate, polycaprolactone, etc., can be utilized as matrices to produce green composites. Meanwhile, natural fibers have been used as fillers for green composites as they are biodegradable and renewable. In this brief review, the physicochemical properties of selected biodegradable polymer, specifically polybutylene succinate, are demonstrated. Moreover, examples of natural fibers that are usually used to produce green composites are also shown. Additionally, practical methods employed for the preparation of green composites were exposed. The tensile properties of green composites, such as the tensile strength, tensile modulus, and elongation at break at different loadings of natural fibers, are also briefly reviewed. The information obtained in this review provides detailed differences in the preparation methods of green composites. In addition, this brief review supplies a clearer comprehension of the tensile properties of green composites for the usage of semistructural and packaging applications. © The Author(s) 2023. All rights reserved.